PERAN REVOLUSI INDUSTRI DALAM MENINGKATKAN KESEJAHTERAAN UMAT MENURUT ISLAM - Irgi Iqbal; Zainarti Zainarti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The Industrial Revolution has brought significant transformation in various aspects of life, including economic, social and technological. In the Islamic context, the welfare of the people is not only measured by material prosperity, but also spiritual and social balance. This article explores the role of the Industrial Revolution in improving the welfare of the people through the application of Islamic economic principles. By utilizing modern technologies such as artificial intelligence and automation, Muslims have the opportunity to create a sustainable and ethical industry, in accordance with sharia values. However, the main challenge is integrating technological advances with Islamic principles, such as social justice and equitable distribution of wealth. This article highlights the importance of wise adaptation and implementation of innovations that are in line with Islamic teachings to achieve comprehensive prosperity for the Ummah. This study contributes to a deeper understanding of how the industrial revolution can be utilized ethically and sustainably to support the welfare of the people from an Islamic perspective